Combating Sex Trafficking: The Role of the Hotel—Moral and Ethical Questions - Jeng, Chu-Chuan (Religions, 2022)
Legitimate companies are key facilitators of human trafficking. These corporate facilitators include not only websites providing advertisements for commercial sex services but also hotels and motels. Analysis of all active federal criminal sex trafficking cases in 2018 and 2019 reveals that in approximately 80% of these cases, victims were exploited at either hotels or motels. This paper studies the prevalence of the hospitality industry in the crime of sex trafficking and the failure of this industry to address this problem until recent civil suits were filed by victims against individual hotels and chains. Drawing on the civil cases filed in federal courts by victims of human trafficking between 2015 and 2021 along the East Coast of the United States, this paper assesses the characteristics of these hotels and the conditions in the hotels that facilitated sex trafficking. The paper then explores the moral and ethical problems posed by the facilitating role of hotel owners/operators in sex trafficking either through collusion or failure to act on and/or report evidence of individual abuse. Suggestions on how to address the problem are provided.